Effects of Hole-Perpendicularity Error on Joint Stiffness of Single-Lap Double-Bolt Composite Joints - LIU, Xueshu; YANG, Yuxing; GAO, Hang; BAO, Yongjie; LI, Rupeng; CHEN, Lei (Engineering Transactions, 2017)
To investigate the influence of hole-perpendicularity error on stiffness of single-lap double-bolt composite joints, a finite element model was first created and validated by using the analogical mass-spring based model proposed by McCarthy et al. The model was then modified by introducing hole-perpendicularity error, with which the influences of holeperpendicularity error, which is represented by hole-titling angle, hole-tilting direction, and bolt torque on the joint stiffness are studied. It is found that the hole-tilting direction causes the joint stiffness to either increase or decrease, which depends on the relation between the hole-tilting direction and the loading orientation. In addition, the hole-tilting angle strengthens the influence of hole-tilting direction and the bolt torque plays the most important role among the three factors in affecting the joint stiffness.